PEMANFAATAN EKSTRAK BUNGA KECOMBRANG (Etlingera elatior jack R.M.sm) SEBAGAI LARVASIDA NYAMUK (Culex quinquifasciatus Say) - Indra Rahmawati; Bagus Uda Palgunadi; Lailia Dwi Kusuma Wardhani; Ni Made Dewi Lestari (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2020)
This study aims to determine the effectiveness of kecombrang flower extract (Etlingera elatior jack R.M.sm) on the death of Culex quenquefasciatus Say larvae. Experimental animals used were Culex quenquefasciatus Say larvae, amounting to 625 tails. The design used was a randomized complete design with 5 treatments and 5 replications. The five treatments consisted of two test groups, namely the treatment group consisting of concentrations of 5%, 10%, 15%, and the control group consisting of positive control namely abate and negative control namely aquades. Observation of mosquito larvae death was done every 2 hours for 12 hours. The data obtained were analyzed using the one-way ANOVA test and continued with the Duncan test. Based on the results of the one way ANOVA calculation the value of sig.0.00 <0.05 means that there are significant differences between treatments. Duncan test results on the treatment of 10% and 15% kecombrang flower extract have the ability as a larvicide high and equal to positive control (abate). Based on the results of the study it was concluded that the extract of kecombrang flower (Etlingera elatior jack R.M.sm) had the ability to larvae against the Culex quenquefasciatus Say mosquito.